1996
DOI: 10.3354/meps130001
|View full text |Cite
|
Sign up to set email alerts
|

Tidal, diel and longer term changes in the distribution of fishes on a Scottish sandy beach

Abstract: ABSTRACT. Fishes were sampled by seine and beam trawl over tidal and diel cycles on a sandy beach on the west coast of Scotland in J u n e and August Species composition of the catches of the 2 gear types differed. There was a signif~cant pos~tive relationsh~p between depth (0 to 5 m ) and species richness but a few specles were restricted to depths of < S m Although s~gnif~cantly more species and individuals were caught at night and at low tide there was no evidence for the existence of d~stinct 'day' and 'ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
9

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 37 publications
5
80
0
9
Order By: Relevance
“…Not all animals move inshore with a rising tide (Gibson et al, 1996) and an inshore assemblage may be composed of animals with varying dependencies on periodically available intertidal resources. Janssen and Kuipers (1980) sampled common shrimp (Crangon crangon) in the Wadden Sea, Netherlands, at a range of water depths and found that only 5% of the population made extensive tidal excursions.…”
Section: 3l Tidal Excursionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Not all animals move inshore with a rising tide (Gibson et al, 1996) and an inshore assemblage may be composed of animals with varying dependencies on periodically available intertidal resources. Janssen and Kuipers (1980) sampled common shrimp (Crangon crangon) in the Wadden Sea, Netherlands, at a range of water depths and found that only 5% of the population made extensive tidal excursions.…”
Section: 3l Tidal Excursionsmentioning
confidence: 99%
“…The most commonly reported ontogenetic changes in movement patterns are associated with refuge function, predation pressure, physiological requirements and diet, all of which are usually associated with increasing body size (Werner and Gilliam, 1984;Dahlgren and Eggleston, 2000). For many species, significant shifts in space-use patterns are reported to occur within the first few weeks and months after settlement, when movement patterns are often represented by a strong sizedepth relationship (Ruiz et al, 1993;Gibson et al, 1996Gibson et al, , 2002. For example, after settlement, plaice (Pleuronecles platessa) in the North Sea concentrate in shallow waters (< 1 m deep) and show a positive relationship between body length and water depth (Gibson et al, 2002).…”
Section: Ontogenetic Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporal variation is assumed to be concentrated at periodic scales, e.g. tidal, diel, lunar, seasonal and annual (Laevastu and Hayes 1981), with numerous studies reporting high contrasts in catches and species richness of estuarine and coastal marine fishes at these Annual and Monthly Variation in Species Composition and Catches of Fishes from the Tabusintac River Estuary in the Southern Gulf of St. Lawrence scales (Dahlberg and Odum 1970;Gibson et al 1996;Lazzari et al 1999;Methven et al 2001;deBruyn and Meeuwig 2001).…”
mentioning
confidence: 99%
“…There are many reasons for juvenile and small-sized fishes to approach shallow and coastal areas. One of these reasons is the search for shelter and refuge from predators in subtidal zones (Wright, 1989;Gibson et al 1996;Pesanha et al 2003b;Dulcic et al 2004). Also, it is believed that the lack of larger fish at night is related to the low depth of the beach, which is naturally shallow.…”
Section: Discussionmentioning
confidence: 99%